Immediate and Long‐Lasting Impacts of the Mt. Pinatubo Eruption on Ocean Oxygen and Carbon Inventories. Issue 2 (4th February 2023) - Fay, Amanda R.; McKinley, Galen A.; Lovenduski, Nicole S.; Eddebbar, Yassir; Levy, Michael N.; Long, Matthew C.; Olivarez, Holly C.; Rustagi, Rea R.
Abstract: Large volcanic eruptions drive significant climate perturbations through major anomalies in radiative fluxes and the resulting widespread cooling of the surface and upper ocean. Recent studies suggest that these eruptions also drive important variability in air‐sea carbon and oxygen fluxes. By simulating the Earth system using two initial‐condition large ensembles, with and without the aerosol forcing associated with the Mt. Pinatubo eruption in June 1991, we isolate the impact of this volcanic event on physical and biogeochemical properties of the ocean. The Mt. Pinatubo eruption forced significant anomalies in surface fluxes and the ocean interior inventories of heat, oxygen, and carbon. Pinatubo‐driven changes persist for multiple years in the upper ocean and permanently modify the ocean's heat, oxygen, and carbon inventories. Positive anomalies in oxygen concentrations emerge immediately post‐eruption and penetrate into the deep ocean. In contrast, carbon anomalies intensify in the upper ocean over several years post‐eruption, and are largely confined to the upper 150 m. In the tropics and northern high latitudes, the change in oxygen is dominated by surface cooling and subsequent ventilation to mid‐depths, while the carbon anomaly is associated with solubility changes and eruption‐generated El Niño—Southern Oscillation variability. We do not find significant impact of Pinatubo on oxygen or carbon fluxes in the Southern Ocean; but this may be due to Southern Hemisphere aerosol forcing being underestimated in Community Earth System Model 1 simulations. Plain Language Summary: The eruption of Pinatubo in June of 1991 produced sunlight‐reflecting aerosols in the upper atmosphere and led to a cooling of the planet for several years. While the global cooling following the eruption is well documented, the impact of the eruption on the ocean oxygen and carbon budgets has received comparably little attention. As the global ocean oxygen concentration is declining in response to climate change, and as the ocean's continued storage of anthropogenic carbon is critical for the climate system, it is of interest to quantify the effect of the eruption on both oxygen and carbon in the global ocean. Here, we use an Earth system model to simulate the historical evolution of the climate system both with and without the Mt. Pinatubo eruption. By comparing the simulations, we are able to quantify the effect of the eruption on ocean properties. We find that the eruption led to cooler surface ocean temperatures, and increases in the ocean oxygen and carbon concentrations that persisted for many years. Our simulations can also be used to study other Earth system changes caused by the eruption. Key Points: Two initial‐condition large ensembles are used to quantify the ocean physical and biogeochemical response to the eruption of Mt. Pinatubo Oxygen is immediately absorbed into the upper ocean and transits to depth where it permanently increases the interior inventory by 60 Tmol Mt Pinatubo forced an increase in the ocean carbon sink of −0.29 ± 0.14 Pg C yr −1 in 1992